Outcomes of limb and life in patients with acute lower limb ischema presenting before and after the “golden six hours” - Nekkanti, Murali Krishna; ., Vivekanand; Suresh, Kalkunte R.; Motukuru, Vishnu; Kolalu, Sumanthraj; Kabra, Aadarsh (International Journal of Advances in Medicine, 2018)
Background: Acute limb ischemia (ALI) is any sudden decrease in limb perfusion causing a potential threat to limb viability. It is generally accepted that in a patient without underlying arterial disease who develops an acute arterial blockage has approximately six hours for revascularisation before irreversible damage occurs. This study endeavoured to analyse and evaluate the causes and clinical outcome of acute lower limb ischemia. Methods: 80 successive patients visiting Jain Institute of Vascular Sciences, Bangalore who were diagnosed to have ALI were included in this prospective study. Thromboembolectomy was performed in 48% of patients, 9% of patients were managed with anticoagulation alone, 8% of patients were treated by catheter directed thrombolysis and primary amputation was inevitable in 16 patients of class III ischemia. Results: All the five patients who presented within the golden six hours survived and their limbs could be salvaged without any morbidity. Even in patients with delayed presentation but viable limb (47 patients) functional limb salvage was possible in 39 patients (82.9%). Overall there was 72.73% limb salvage and 27.27% patients underwent amputation. There was a mortality rate of 13.16% in the study. Conclusions: Overall there was 72.73% limb salvage and 27.27% patients underwent amputation. Revascularization within six hours is ideal (only 6.25% of patients in our study); however, in delayed presentation (93.75%), physiological state of the limb, rather than elapsed time from onset of occlusion will determine the operability. Late revascularization may thus be indicated and is often successful if limb still exhibits signs of viability.